FORENSIC ACCOUNTING AS AN INSTRUMENT FOR FRAUD DETECTION AND PREVENTION IN THE PUBLIC SECTOR: MODERATING ON MINISTRIES, DEPARTMENTS AND AGENCIES IN NIGERIA - Niyi Oladipo Olaniyan; Ayodele Temitope Ekundayo; Oladimeji Emmanuel Oluwadare; Theresa Omolade Bamisaye (Acta Scientiarum Polonorum. Oeconomia, 2021)
The study examined forensic accounting as an instrument of detection and prevention of fraud in Nigeria. It specifically examined the influence of forensic accounting on detection and prevention of fraud in Ministries, Departments and Agencies in Nigeria. The study is predicated on policeman theory, white collar theory, fraud diamond theory. Primary sources of data were employed which covered the period of ten (10) years spanning from 2010 to 2020. A cross sectional Survey design was adopted. A Questionnaire was used in data collection from the staff of Integrated Personnel Payroll Information System and Office of the Account General of Federation. Seventy-five (75) questionnaires were used as the sample size. The study adopts descriptive statistics while regression analysis was used to test the stated hypotheses. The result of the findings showed that forensic accounting has positive and significant influence on fraud prevention, but foreign account has no total control on fraud detection. It was also revealed that forensic litigation has no significant positive influence on recovery of funds lost to fraud. The study recommends that forensic accounting systems should be allowed as a procedure for internal control systems so as to prevent or reduce the level of income leakages, mismanagement of funds and budget padding.